2013
DOI: 10.1016/j.neurobiolaging.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Visual contrast sensitivity in Alzheimer’s disease, mild cognitive impairment, and older adults with cognitive complaints

Abstract: Deficits in contrast sensitivity (CS) have been reported in Alzheimer’s disease (AD). However, the extent of these deficits in prodromal AD stages, including mild cognitive impairment (MCI) or even earlier, has not been investigated. In this study, CS was assessed using frequency doubling technology (FDT) in older adults with AD (n=10), amnestic MCI (n=28), cognitive complaints without performance deficits (CC, n=20), and healthy controls (HC, n=29). The association between CS and cognition was also evaluated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 73 publications
8
79
1
1
Order By: Relevance
“…Risacher et al (2013) reported that contrast sensitivity disturbances are present even in the early stages of AD (even in mildly cognitively impaired patients); they further demonstrated a correlation between contrast sensitivity (the FDT-2 24-2 VF contrast sensitivity test) and the MMSE score. We also found a strong significantly positive correlation between the Colour Confusion Index (CCI) with the Lanthony 15D test and disease duration (0.973, p = 0.027).…”
Section: Referencesmentioning
confidence: 89%
“…Risacher et al (2013) reported that contrast sensitivity disturbances are present even in the early stages of AD (even in mildly cognitively impaired patients); they further demonstrated a correlation between contrast sensitivity (the FDT-2 24-2 VF contrast sensitivity test) and the MMSE score. We also found a strong significantly positive correlation between the Colour Confusion Index (CCI) with the Lanthony 15D test and disease duration (0.973, p = 0.027).…”
Section: Referencesmentioning
confidence: 89%
“…45 They found that patients with AD and MCI showed marked deficits in FDT testing, such as increased test duration, reduced general sensitivity (lower MD), and abnormal variability (higher PSD). These results are compatible with our results.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that FDT testing can be used as a biomarker for AD. 45 Automated perimetry requires considerable patient cooperation and many patients with mild AD can still produce reliable VF results despite their cognitive deterioration. Our experience with FDT testing in AD taught us that it was difficult to obtain reliable results in patients with moderate to severe cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…As well as HL, loss of vision is also a part of normal aging (e.g., Risacher et al, 2013;Heyl & Wahl, 2012). Wearing glasses can cause problems with eye tracking (Eachus, Cassidy, Norgate, Marrow, & Greene, 2008;O'Brien & Sharon, 2009), and this consideration restricted our potential participants.…”
Section: Hl Population and Recruitment Of Participantsmentioning
confidence: 99%
“…Apart from HL, normal consequences of aging also include declining visual abilities, such as visual acuity and contrast sensitivity (e.g., Risacher et al, 2013;Heyl & Wahl, 2012) and cognition (e.g., McDowd & Shaw, 2000;Verhaeghen et al, 2003;Mayr et al, 2001;Verhaeghen et al, 2005, Craik & Salthouse, 2000Phillips & Lesperance, 2003). Relationships between sensory and cognitive losses in older adults have also been presented (Clay et al, 2009;Heyl & Wahl, 2012;Holland, 2009;Vreeken et al, 2013).…”
Section: Pretestsmentioning
confidence: 99%